Inhibition of the RIP3/MLKL/TRPM7 necroptotic pathway ameliorates diabetes mellitus-induced erectile dysfunction by reducing cell death, fibrosis, and inflammation - Niu, Lipan; Yang, Pei; Zhu, Bingbing; Jin, Xiufang; Yang, Chengxia; Zhang, Xijia; Liu, Yulian; Zhang, Rui; Liu, Fengxia (Frontiers in Pharmacology, 2024)
Diabetes mellitus-induced erectile dysfunction (DMED) is a common complication in patients with diabetes mellitus. Necroptosis is regarded as a form of cell death that is intimately associated with the inflammatory response, which is not only initiated by inflammatory factors such as TNF-α, but also triggers the inflammatory cascade through the rupture of the dying cell. There is no definitive study on the role of necroptosis in the pathological process of DMED. In light of the pathological features of high inflammation levels in DMED patients, we assessed whether the necroptosis plays an important role in the course of DMED. Our study revealed that penile tissues of DMED rats showed high levels of key necroptosis factors such as receptor-interacting protein kinase 3 (RIP3), mixed-lineage kinase domain-like protein (MLKL), and transient receptor potential melatonin 7 (TRPM7). Furthermore, the inhibition of necroptosis with a receptor-interacting protein kinase 3 (RIP3) inhibitor or Yimusake (a common herbal remedy for ED) effectively rescued damage to corpus cavernosum smooth muscle cells (CCSMC) under high glucose conditions. Our findings suggest that inhibition of the RIP3/MLKL/TRPM7 necroptotic pathway could effectively ameliorate CCSMCs fibrosis and death induced by high glucose and inhibited the inflammatory response.